1988
DOI: 10.1002/clc.4960110213
|View full text |Cite
|
Sign up to set email alerts
|

Malignant schwannoma of the heart

Abstract: Summary:Primary cardiac tumor is an extremely rare disease entity. Only three cases of primary malignant cardiac schwannoma, the subject of this report, have been recorded in Japan. Recently, we encountered a case of malignant schwannoma in which retention of pericardial effusion was the first clinical finding. This case was a 30-year-old female, who had dyspnea at work, general fatigue, and fever. Striking cardiac expansion was seen, with a cardiothoracic ratio (CTR) d 6 9 % on chest x-ray. Twodimensional ech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
25
0
3

Year Published

2003
2003
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 1 publication
0
25
0
3
Order By: Relevance
“…Neurogenic cardiac tumors are extremely rare, and they are almost always benign and primary, although they may sometimes present as malignant, [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] multiple malignant, 11,13 and metastatic tumors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Neurogenic cardiac tumors are extremely rare, and they are almost always benign and primary, although they may sometimes present as malignant, [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] multiple malignant, 11,13 and metastatic tumors.…”
Section: Discussionmentioning
confidence: 99%
“…4 However, it can be found in the left atrium, protruding from the left atrium into the left ventricle during diastole, 6 or near the left ventricle. 8 Symptoms are related to its location; in fact, extrinsic compression and pericardial effusion (often hemorrhagic) may occur when it is located in the atrial wall or in the pericardial sac, or it may lead to valvular obstruction when it is inside the atrial chamber. When the hepatic veins or the vena cava are obstructed, signs of cardiac failure may appear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Primary neurogenic tumors of the heart originating in the nerve sheath are extremely uncommon, and to date, 10 cases of neurilemomas, or schwannomas, have been reported. [1][2][3][4][5][6][7][8] We report the case of a patient with a right atrial tumor who underwent a successful resection; histological examination revealed a benign primary schwannoma of the heart.…”
mentioning
confidence: 99%
“…Symptoms also depend on the size, the rate of growth, and how promptly they are detected and removed. The most common clinical findings are chest pain, dyspnea, orthopnea, distal edema, syncope, arrhythmias, and conductive disorders, and these symptoms are frequently associated to pericardial effusion 1,5 and acute atrial fibrillation. 6 Nevertheless, cardiac schwannomas can have a benign and asymptomatic presentation, such as in the patient reported here, as well as in other previously reported cases, 8 where early identification and consequently smaller tumor size or location favored a lack of symptoms.…”
mentioning
confidence: 99%